Assessment of genetic diversity of different tomato genotypes using RAPD markers (Progressive Agriculture, 2019)
The present investigation was carried out for assessment of genetic diversity among the 28 tomato genotypes though three random amplified polymorphic DNA (RAPD) markers. A total of 15 distinct DNA fragments ranging form 100-1000 bp were amplified by using three selected primers of which 5.00 polymorphic bands per primer and over all polymorphic loci was 100 percent. The extent of genetic diversity among these genotypes was computed through parameters of genetic diversity and Shanon’s information indices. The highest genetic distance was observed among the accession Cl-3d-0-99 (V93)  vs. F1 (G X V12), F1 (G X V17), F1 (G X V29) and  Durch fuegel  (G) vs. F1 (G X V17) and F1 (G X V93) vs. F1 (G X V12), F1 (G X V17), while the lowest genetic distance was observed among the accessions Fut. Wed Abrid (V94) vs. Sunlight pole (V67) and F1 (V67 X VG) vs. F1 (V17 X VG), F1 (V93 X VG) and F1 (V93 X V17) vs. F1 (V17 X VG), F1 (V67 X VG), F1 (V93 X VG). The Unweighted Pair Group Method of Arithmetic Mean (UPGMA) dendrogram based on Nei’s genetic distance divided the genotypes into two main clusters: A & B. Cluster ‘A’ consists of 19 accessions and cluster ‘B’ consists of 9 accessions. The information generated from this study could be useful in gene mapping and marker assisted breeding for future tomato breeding programs.Progressive Agriculture 29 (4): 276-283, 2018